Dietary Diversity among Students of Khulna University, Bangladesh - Mymuna Islam Moon; Tanjirul Islam; Mortuja Mahmud Tohan; Bristi Rani Shah; Nushrath Jahan Juhi; Tayeeba Tabussum Anni; Abu Mohammad Mujahidul Islam; Kazi Moushumi Akter; Md. Hasan Howlader; Md. Ashfikur Rahman (Dr. Sulaiman Al Habib Medical Journal)
Background: A healthy diet is a fundamental component of a healthy lifestyle, with dietary diversity being a crucial aspect of nutritious diets. Undergraduate students often exhibit inadequate dietary habits due to insufficient parental monitoring, lack of understanding of nutrition and proper eating habits, and the stress associated with academic, professional, and social obligations. Objective: This study aimed to measure the dietary diversity of the university students and to determine the factors associated with dietary diversity. Methods: This quantitative cross-sectional study was conducted with a sample of 240 students from Khulna University, Bangladesh. Dietary diversity was chosen as the dependent variable measure on the standard dietary diversity scale (DDS) of the Food and Agriculture Organization. The DDS comprises nine food group markers, with possible scores ranging 0–9. Each food group item consumed is given a score of 1, and the maximum score a respondent can achieve on any one day is 9. Independent variables included demographic and socioeconomic factors, diet patterns, and intake of main meals in the last 24 hours. The respondents were selected by a simple random sampling method and the data were gathered via a questionnaire survey. Descriptive statistics, one-way analysis of variance (ANOVA), and binary logistic regression were conducted for data analysis. Results: The study assessed the prevalence of minimum dietary diversity among students, revealing that 55.8% had a sufficient dietary diversity score, while 44.2% scored poorly. Notably, students aged 21–25 years exhibited greater dietary diversity, particularly those in the third year of graduation or pursuing master’s degrees. The majority of these students hailed from urban areas (60.8%), consumed three main meals a day, and had notable snacking habits. Snacking choices varied with responses, including fast food, beverages, chocolates, biscuits, and fruits. Notably, 47.1% of students addressed their immediate hunger based on availability, whereas 33% admitted to skipping breakfast within the last 24 hours. These factors emerged as influential contributors to the prevalence of dietary diversity. Conclusion: The study revealed that nearly half of the students had poor dietary diversity, which signifies a critical problem. University administrations and policymakers are urged to consider the demographic and socioeconomic conditions of students and take necessary measures to improve their dietary patterns, ultimately enhancing overall dietary habits.